Effect of Training on Hazard Prevention on Performance of Cement Manufacturing Firms in Kenya - Mwaruta, Selerina Samba; Karanja, Patrick Ngugi; Kamaara, Mary (Research Publish Journals, 2019)
This study sought to find out the effect of hazard prevention training on the performance of cement manufacturing companies in Kenya. Manufacturing firms are spending a lot of money to take care of their workers’ absenteeism and compensation which is caused by occupational accidents. It has been argued that lack of hazard prevention training has majorly contributed to the continued losses to the companies due to occupational accidents among the employees. It therefore becomes necessary to assess the effect of hazard prevention training on the performance of manufacturing companies in the cement sub-sector in Kenya. The study adopted the descriptive research design which used both quantitative and qualitative approach to determine the relationship between employee training and Performance of Cement Manufacturing firms in Kenya. The study adopted a sampling formula to identify 344 as the appropriate sample size and the respondents were picked through stratified random sampling. Data was collected using a structured questionnaire for employees that had both openended and close-ended questions. Hypotheses were tested using linear regression, multiple regression analysis. The study established that hazard prevention training had significant and positive effect on performance of cement manufacturing firms in Kenya. The study also established that management styles had significant moderating effect on the relationship between hazard prevention training and performance of cement manufacturing firms in Kenya. The study concluded that as a result of hazard prevention training, the awareness on how to prevent hazard was enhanced thus preventing occupational accidents and promoting employee productivity. The study recommended that there was considerable need to provide training on need hazard prevention to the employees so as to avoid work-related accidents and promote performance.
Keywords: Hazard Prevention; Training; Management Style; firm Performance; Cement Manufacturing Firms; Occupational Health and Safety